Magnesium Solubility in Primary α-Al and Heat Treatment Response of Cast Al-7Si-Mg - Jorge Santos; Arne K. Dahle; Anders E. W. Jarfors (Metals, 2020)
Magnesium and silicon concentrations in the interior of primary α-Al of Al-7Si-Mg alloys were studied at temperatures in the liquid-solid range and just after solidification was completed. Analysis of the results showed that the magnesium concentration in the interior of primary α-Al is very low in the temperatures range from the liquidus to the start of the Al-Si eutectic reaction. Formation of silicon-rich phases during eutectic reactions, such as eutectic silicon and β-Al5FeSi, phases trigger a significant increase in the magnesium concentration in the interior of primary α-Al, when sufficient time is allowed for solid-state diffusion to occur. When fast cooling rates are applied during the Al-Si eutectic reaction, most of the magnesium is retained in π-Al8FeMg3Si6 and Mg2Si phases formed during solidification. Semi-solid Al-7Si-Mg castings were produced with varying magnesium contents, and the mechanical properties were evaluated in the as-cast, T5 and T6 conditions. It was found that the 0.2% offset yield strength of the semi-solid Al-7Si-Mg castings in the T5 and T6 conditions increases linearly with the square root of the magnesium concentration in the interior of the α-Al globules formed during the slurry preparation process.